From values to action: the critical mediation of green brand image in green cosmetics purchase behaviour - Maharani, Shabira; Damarani, Zelika Nidya; Nurdianasari, Rista (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
Despite the growing interest in sustainable beauty products, many consumers still do not translate this interest into actual purchases of eco-friendly products. This study examines how three perceived consumer values environmental, quality, and social value shape green brand image and how that image drives actual purchase behavior in the Indonesian green cosmetics market. A cross-sectional online survey was conducted with female consumers (N = 160) who had purchased green cosmetics within a recent period. The data were analyzed using SEM–AMOS. A set of nineteen verified measurement items was employed to evaluate the five underlying constructs using a 10-point scale. Structurally, all three values were found to have a positive influence on green brand image, and green brand image significantly predicted purchase behavior. The analysis also confirmed that green brand image mediates the influence of environmental value, quality value, and social values on purchase behavior. The constructed model successfully explained over 50% of the variance in both brand image and purchase behavior. The suggested managerial implications include: presenting credible environmental proof, ensuring consistently high product performance, and developing strategies that build social recognition for the brand.